Economic inequality and social class - Stefansson, K (2014)
This thesis is about social class and economic inequality, using the Goldthorpe class schema. It tests theories claiming that social class is increasingly irrelevant to inequality and people's life-chances with data on incomes and material living standards from the British Household Panel Survey. It covers the period over which the survey ran, i.e. 1991-2008. During this time many prominent social theories dismissed class analyses while others sought to retain the class concept but dismissed its economic foundations, seeking to ground it in culture instead. Economic inequality has not figured highly on the agenda of class analysts, at least not those working with the Goldthorpe class schema. There is a substantial body of work on mobility, voting behaviour, income poverty and material deprivation, but inequality in a broader sense has for the most part been neglected. This thesis is a step towards rectifying this situation. Thus it provides new information about within-career social mobility as well as income inequality within and between classes, on whether income mobility reduces class inequalities over time, and cast light on class inequalities in material living standards. The findings suggest that class is far from irrelevant to economic inequality. Class differences in incomes are persistent, between class inequalities contribute more to inequality overall than within-class inequalities, and while income mobility does reduce class inequalities over time it is not to the extent that supports the hypothesis that class is irrelevant to people's economic fortunes.